ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROCUREMENT FRAUD: SEBUAH KAJIAN DARI PERSPEKTIF PERSEPSIAN AUDITOR INDEPENDEN PEMERINTAH - Dewa Ayu Toga Juliantini; Kadek Dewi Padnyawati (Hita Akuntansi dan Keuangan, 2020)
Procurement fraud is fraud that occurs in the public sector in the form of embezzlement, misappropriation of assets, and false explanations. This study aims to examine the factors that influence procurement fraud: a perspective study of perceived independent government auditors. The population in this study were all auditors at the BPK Office of the Republic of Bali Province Representative, while 40 people were selected as research objects. The sampling technique uses a purposive sampling method. Data were tested using validity test, reliability test, non response bias test, multicollinearity test, heteroscedasticity test, multiple regression analysis, hypothesis test and coefficient of determination. The results showed that the financial pressure variable had a positive and significant effect on procurement fraud. Weaknesses in procurement systems and procedures have a negative and significant effect on procurement fraud. The quality of the procurement committee has no significant effect on procurement fraud. Attitudes towards fraud behavior do not significantly influence procurement fraud. Subjective norms have a positive and significant effect on procurement fraud. The perceived behavioral control has no significant effect on procurement fraud.